Potensi Limbah Penebangan dan Pola Bentuk Penampang Tunggak Pohon pada Kegiatan Pemanenan Kayu di Hutan Alam Produksi Kalimantan Tengah: The Potential of Logging Waste and the Cross-Sectional Shape Patterns of Tree Stumps in Timber Harvesting Activities in Production Forests in Central Kalimantan - Imanuel, Ricky Tri; Junaedi, Ajun; Yosep, Yosep; Dwiastuti, Rini; Yanciluk, Yanciluk; Rizal, Moh (JURNAL HUTAN TROPIKA, 2025)
The objectives of this study were (a) to calculate the volume, percentage, and potential of tree felling waste; and (b) to identify the cross-sectional patterns of tree stumps in timber harvesting activities in the production forests of Central Kalimantan. Measurements of logging waste and observations of tree stump cross-sectional shapes were carried out on 60 predetermined sample trees located within 10 observation plots (10 ha). The results showed that the volume of logging waste was 106.42 m3 or 31.82% with a waste potential of 10.64 m3/ha. The patterns of stump cross-sections found in the logging plots consisted of several shapes, namely: star-shaped, triangular, round, irregular round, and square.